Historical Highlights on Mental Health Education in Iraq - Younis, Maha S. (Journal of the Faculty of Medicine Baghdad, 2019)
This article aims to cast a shadow over the history of mental health education and training in Iraq and a projection of Islamic scientific heritage in Baghdad during the seventh century. It also discloses the foundation of first teaching and training centers in psychiatry focusing on the marked contribution of the pioneer psychiatrists. Introduction. Up to our knowledge there is no elaborate published literature focusing on historical role of Iraq in mental health education and training and its current reality apart from scares data about mental health in Mediterranean region as a whole. In this article, we try calling the attention to the outstanding contribution of Iraq in mental health and medical education in general which appeared to be established during the golden era of Abbasid Caliphs in Baghdad during the seventh century. After several decades of scientific and cultural deterioration associated withOttomans colonization , Baghdad intellectuals started to build the first medical school in Iraq at the end of twentieth century , teaching mental illnesses as part of the curriculum took place and continue to progress through establishing the national training programs .